2011
DOI: 10.1007/978-3-642-25734-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Speed Control of Switched Reluctance Motor Using Artificial Neural Network Controller

Abstract: Abstract. Switched reluctance motors (SRMs) have an intrinsic simplicity and low cost that makes them well suited to many applications. However, the motor has doubly salient structure and highly non-uniform torque and magnetization characteristic. Since it was hard to determine the accurate mathematical model of (SRM) .The Artificial Neural Networks (ANNs) solve the problem of nonlinearity of SRM drive. It ensures fast, accurate, less overshoot and high precision dynamic response with perfect steady state perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Different methods of controllers are implemented in different power system problems including the optimization algorithms [15][16][17][18]. In the implementation stage, many speed control techniques of drive systems such as PI control, sliding mode control and artificial neural network control applied in SRM are suggested [19][20][21]. However, PI based control method is commonly adopted due to the advantages such as the easiness of the implementation of control strategy, precise control in the transient and steady state period of operation etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different methods of controllers are implemented in different power system problems including the optimization algorithms [15][16][17][18]. In the implementation stage, many speed control techniques of drive systems such as PI control, sliding mode control and artificial neural network control applied in SRM are suggested [19][20][21]. However, PI based control method is commonly adopted due to the advantages such as the easiness of the implementation of control strategy, precise control in the transient and steady state period of operation etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SRM nonlinearity characteristics are trained by neural networks and then the current graph for ripple reduction is obtained. ANN is used as an intelligent controller [18,19]. Torque ripple reduction is done through PI and fuzzy logic controller [20].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies the authors have shown that SOM (Self-organizing Maps), GMM (Gaussian Mixture Model), etc., can identify the different working conditions of rolling bearings [3,4]. Meanwhile, traditional ANN (Artificial Neutral Network), BP (Back Propagation) and Elman models have been widely used in the field of intelligent prediction of rotating machinery [5][6][7]. But some of the methods mentioned above are complex and time consuming, such as GMM, meanwhile, some are too simple to get approving results, like BP, etc.…”
Section: Introductionmentioning
confidence: 99%